International economics - Salvatore, Dominick (Wiley, 2001)
This text presents an evenhanded, unbiased, intuitive coverage of all the standard topics as well as the latest theoretical and policy issues in international economics. The chapters feature an intuitive approach with more rigorous proofs presented in chapter appendices. Throughout the text, the author maintains a tight connection with the real world with 108 real-world case studies, many brand new to this edition.